2013
DOI: 10.1155/2013/951415
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroprotective Effect ofMoringa oleiferaagainst Focal Ischemic Stroke Induced by Middle Cerebral Artery Occlusion

Abstract: The protection against ischemic stroke is still required due to the limitation of therapeutic efficacy. Based on the role of oxidative stress in stroke pathophysiology, we determined whether Moringa oleifera, a plant possessing potent antioxidant activity, protected against brain damage and oxidative stress in animal model of focal stroke. M. oleifera leaves extract at doses of 100, 200 and 400 mg·kg−1 was orally given to male Wistar rats (300–350 g) once daily at a period of 2 weeks before the occlusion of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…It has been shown that treatment by antioxidant and anti‐inflammatory agents has been able to impede sensorimotor dysfunction . In this regard, our findings indicate that the antioxidant and anti‐inflammatory activities of α‐pinene are attributed to attenuation of neuronal injury and improvement in neurobehavioural functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that treatment by antioxidant and anti‐inflammatory agents has been able to impede sensorimotor dysfunction . In this regard, our findings indicate that the antioxidant and anti‐inflammatory activities of α‐pinene are attributed to attenuation of neuronal injury and improvement in neurobehavioural functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of GPx activity was carried out by using Glutathione Peroxidase Assay Kit. GPx activity was measured according to a decrease in absorbance at 412 nm owing to the oxidation of NADPH to NADP + …”
Section: Methodsmentioning
confidence: 99%
“…Kirisattayakul et al . () have demonstrated that a hydroalcohol extract of M . oleifera leaves at oral doses of 100–400 mg/kg for 3 weeks attenuated brain dysfunction and brain damage induced by cerebral ischemia.…”
Section: Animal and In Vitro Studiesmentioning
confidence: 97%
“…According to another study where CIR was induced by occlusion of middle cerebral artery occlusion (MCAO) in rats [80], it was demonstrated that M. oleifera leaf extract, when orally administered, protected against brain damage, by decreasing infarction volume in both cortex and subcortex regions and against oxidative stress, by modulating MDA level, and the activities of SOD, CAT, and glutathione peroxidase (GPx) [80].…”
Section: Itcs In Ischemic Brain Injurymentioning
confidence: 99%